Looking at non-sensory factors underlying consumers' perception of smoked bacon - Saldaña E. (2020)
Smoked bacon is a food consumed everywhere and previous work has focused on the sensory properties and acceptability of the product. However, little attention has been given to the non-sensory factors that drive sensory and hedonic perception of this product. In this context, the aim of this work was to study the influence of non-sensory factors on consumer behavior towards smoked bacon, using projective mapping coupled with conjoint analysis. Eight visual stimuli were created using a full factorial design with three factors (convenience, healthiness, and context of consumption), at two levels each. Ninety-five consumers positioned the stimuli in a two-dimensional space considering their similarities and differences, and then, rated their expected liking and purchase intention. According to the projective mapping, consumers based the representation of the stimuli on the three factors under study, but conjoint analysis indicated that healthiness was the most important factor, followed by the context of consumption and convenience. The findings of this study may help in the selection of future strategies in the process of food development, in order to launch products with greater chance of success in the market. © 2020 Elsevier Ltd